Identifying Causes of Pressure Drop in Heat Exchanger E-204: Menganalisis Penyebab Penurunan Tekanan pada Penukar Panas E-204 - Fernanda, Ardhi Shefta; Firdaus, Rachmat (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the efficacy of preventive maintenance measures on the E-204 Plate Heat Exchanger (PHE) to mitigate pressure drop issues affecting production efficiency and operational costs in the petrochemical industry. The research identifies gasket leaks and plate blockages as primary contributors, attributed to wear and dirt deposits. Through periodic inspections, gasket replacements, and mechanical and chemical cleaning, maintenance interventions were executed. Results demonstrate a significant reduction in gasket blockages and leaks, leading to improved fluid flow and operational efficiency. The findings underscore the importance of regular preventive maintenance in ensuring optimal PHE performance and cost-effective operations. Highlight : Maintenance Intervention: Periodic inspections, gasket replacements, and mechanical and chemical cleaning were implemented to address gasket leaks and plate blockages. Enhanced Efficiency: The study resulted in a significant reduction in gasket blockages and leaks, leading to improved fluid flow and operational efficiency. Implications for Industry: Regular preventive maintenance is crucial for optimal performance and cost-effective operations in petrochemical production processes. Keywords: Plate Heat Exchanger, Preventive Maintenance, Efficiency Improvement, Gasket Leaks, Petrochemical Industry